1985
DOI: 10.1016/0006-8993(85)90377-4
|View full text |Cite
|
Sign up to set email alerts
|

‘Gating’ of somatosensory evoked potentials begins before the onset of voluntary movement in man

Abstract: Key words: somatosensory evoked potential --gating --voluntary movement --afferent somatosensory information --inputThe inflow of somatosensory information to the cerebral cortex is modified before and during active movement in animals. This phenomenon has been termed 'gating' and occurs at several levels of the sensory pathway. We studied somatosensory evoked potentials (SEPs) to stimulation of the median nerve at the wrist during voluntary movement of the ipsilateral thumb in man. Results indicate that SEPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 9 publications
5
53
1
Order By: Relevance
“…Transient reductions in SEPs have been reported previously in conjunction with finger and limb movement (Papakostopoulos et al 1975;Rushton et al 1981;Starr and Cohen 1985). The reduction has been attributed to the idea that the nervous system suppresses sensory inflow associated with self-initiated movement.…”
Section: Discussionmentioning
confidence: 78%
“…Transient reductions in SEPs have been reported previously in conjunction with finger and limb movement (Papakostopoulos et al 1975;Rushton et al 1981;Starr and Cohen 1985). The reduction has been attributed to the idea that the nervous system suppresses sensory inflow associated with self-initiated movement.…”
Section: Discussionmentioning
confidence: 78%
“…It has been reported that cortical somatosensory evoked potentials are decreased in amplitude during movement (Giblin 1964;Coquery and Vitton 1972;Hazemann et al 1975;Papakostopoulos et al 1975;Rushton et al 1981;Chapman et al 1984;Start and Cohen 1985). One might speculate that if subjective intensity is determined on the basis of the central neural code then, when neural discharge is diminished, there would be a parallel decrease in the subjective intensity of the stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Gating accompanying both the preparation and the act of movement can be accompanied by an attenuation of sensory processes occurring both before and during the motor activity (Starr et al, 1969;Starr and Cohen, 1985). Gating in the auditory system has been shown to be due to both an attenuation of acoustic input accompanying movementrelated contractions of middle ear muscles (Cannel and Starr, 1963) and to changes in central auditory pathway processing (Starr, 1964;Tapia et al, 1987).…”
Section: Processes Acting To Modulate Evoked Potentialsmentioning
confidence: 99%
“…We do not consider gating to be a mechanism accounting for the attenuation of any of the components defined in this study. For instance, an attenuation of N100 follows the motor response to targets and requires 5-10 s before amplitudes are restored, a time period beyond the ms range usually attributed to gating (Starr and Cohen, 1985).…”
Section: Processes Acting To Modulate Evoked Potentialsmentioning
confidence: 99%